Using Online-Based Learning Assessment Applications to Improve The Effectiveness of Distance Education - Menik Kurnia Siwi; Rita Sofyan; Tri Kurniawati (Indonesian Journal of Devotion and Empowerment, 2023)
In each learning process, a teacher must carry out a learning assessment to measure students' ability to the learning given. For learning activities carried out online, a learning assessment is also needed for each of these online learning activities. This activity aims to improve the teacher's ability to apply various online assessment media. Activities were carried out in 8 meetings for training and delivery of material using the online assessment application. The activity results showed an increase in the teacher's ability to compose questions based on HOTs and Thematics. Apart from that, there has also been an increase in the knowledge and ability of teachers in making and operating online learning assessment applications. Pada setiap proses pembelajaran, guru harus melakukan assessment pembelajaran untuk mengukur kemampuan peserta didik terhadap pembelajaran yang diberikan. Untuk kegiatan pembelajaran dilakukan secara online maka dibutuhkan pula assessment pembelajaran untuk setiap kegiatan pembelajaran online tersebut. Tujuan kegiatan ini adalah untuk meningkatkan kemampuan Guru dalam mengaplikasikan berbagai media assessment online. Kegiatan dilaksanakan dalam 8 kali pertemuan untuk pelatihan dan penyampaian materi penggunaan aplikasi assessment online. Hasil kegiatan menunjukkan adanya peningkatan kemampuan guru dalam menyusun soal berbasis HOTs dan Tematik. Selain itu juga terjadi peningkatan pengetahuan dan kemampuan guru dalam membuat dan mengoperasikan aplikasi assessment pembelajaran secara online.